Assessment the knowledge of mothers regarding Diarrhea of Children less than five years at Internally Displaced Persons (IDPs) Arbit camp: A descriptive study - Kasem, Attallah Omer; Abas, Layla Abdulkhalk; Ezzaddin, Shahow Abdulrahman; Ahmed, Ibrahim Tofiq; Saleem, Rozhgar Abdulla; Maulud, Awaz Kamal (Kurdistan Journal of Applied Research, 2017)
Diarrhea is the 2nd chief reason of child death widespread. Low- and middle-income countries are especially exhausting with this both avoidable and treatable condition. Aim: To investigate how children’s health less than five years affected by diarrhea at Internally Displaced Persons (IDPs) in Arbit camp. This study was carried out from december22th 2015 to march 20th 2016. Non-probability sampling a convenience sample of (103) mothers of internally Displaced Persons (IDPs) Arbit camp were selected for the purpose of the study.. It was comprised of two parts; the first part includes the mothers' demographic attributes and the second part assessed the knowledge of diarrhea with (20) yes or on questions. The main results obtained from the study are as follows, more than the half (54.40%) of mothers are (18-25) years old, the (49.50%) of mothers have moderate Socio-economic status, (99.00%of mothers are housewife,, also (54.40%) of the mothers have one child less than five years. The (46.60%) of mothers are illiterate and only (32.00%) of husband read and write and According to the family size of the study (51.50%) of mothers has five children. About the distance of water sources (56.30%) of mothers needs more than 5 minutes to reach water sources, (47.60%) of them have received health education regarding diarrhea held in primary health care center. There was statistically significant relationship between mother’s knowledge of diarrhea and (age group, educational level of husband, educational level of the mother, and occupational status of mother, socioeconomic status, and source of information). So the following recommendation is suggested, highlight the need for excessive nutritional educational program, about diarrhea should be implemented for mothers, good sanitation and improvement of housing conditions especially water resources at arbit camp